2020
DOI: 10.1136/bmjsem-2019-000664
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated care programmes for sport and work participation, performance of physical activities and quality of life among orthopaedic surgery patients: a systematic review with meta-analysis

Abstract: ObjectivesOrthopaedic surgery is primarily aimed at improving function and pain reduction. Additional integrated care may enhance patient’s participation in sports and work, possibly improving performance of physical activities and quality of life (QoL). We aimed to assess the effectiveness of integrated care among orthopaedic surgery patients.DesignSystematic review with meta-analysis.Data sourceMedline, EMBASE and CINAHL (until 17 June 2019).Eligibility for selecting studiesWe searched for controlled studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…These consequences receive little-to-no attention in current clinical guidelines and yet are increasingly important outcomes for patients of working age ( 17 , 18 ). Therefore, occupational health professionals around the world face the urgent challenge to develop evidence of how to improve a patient’s ability for sustained employability – as an essential value in life – after surgery ( 19 ). Promising initiatives have recently been described although not validated for work participation yet ( 20 23 ).…”
mentioning
confidence: 99%
“…These consequences receive little-to-no attention in current clinical guidelines and yet are increasingly important outcomes for patients of working age ( 17 , 18 ). Therefore, occupational health professionals around the world face the urgent challenge to develop evidence of how to improve a patient’s ability for sustained employability – as an essential value in life – after surgery ( 19 ). Promising initiatives have recently been described although not validated for work participation yet ( 20 23 ).…”
mentioning
confidence: 99%
“…Although, the information on the key criterion of the effectiveness of rehabilitation is quite homogeneous. Thus, Р. Coenen, G. Hulsegge, J. G. Daams, et al [7] came to the conclusion that the effectiveness of integrated care programs and rehabilitation for postoperative patients should be measured by their ability to participate in work and sport. Next, the authors conducted meta-analysis, which shows that insufficient attention of researchers to the criterion of returning of postoperative patients to other activities, besides domestic self-care, is the reason for the distortion of data on the quality of rehabilitation.…”
Section: Theoretical Fundamentals Of the Researchmentioning
confidence: 99%
“…Next, the authors conducted meta-analysis, which shows that insufficient attention of researchers to the criterion of returning of postoperative patients to other activities, besides domestic self-care, is the reason for the distortion of data on the quality of rehabilitation. The information presented by the authors [7] is used together with authors' data [10] while choosing the subject of the experimental rehabilitation experiment (teacher), as well as while teaching the students the basics of psychological support of a client.…”
Section: Theoretical Fundamentals Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review demonstrated that the resumption of activities of daily life after knee arthroplasty can be improved with the help of integrated care programs, such as those provided by m/eHealth [18]. m/eHealth has the possibility to provide personalized and adaptive guidance to patients.…”
Section: Time After Knee Arthroplastymentioning
confidence: 99%